Anti-rutting epoxy resin concrete

By using epoxy resin fibers and modified asphalt in concrete, combined with other additives to form covalent bond links and conjugated systems, the problems of low compressive strength and easy aging on existing concrete floors have been solved, and a higher Compression and UV resistance.

CN119430787AInactive Publication Date: 2025-02-14周国力
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411323866.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing concrete floor has low compressive strength and is susceptible to ultraviolet aging, resulting in reduced radial and cracks, especially in areas where vehicles frequently pass through.

Method used

Epoxy resin fibers are mixed with modified asphalt, combined with silicate cement, limestone coarse grains, limestone rock chips, fly ash, triterpene saponin gas induction agent and melamine water reducer, and formed through specific process steps and chemical reactions. Covalent bond linkage and conjugation system improves the compressive and ultraviolet resistance of concrete.

Benefits of technology

It significantly improves the compressive strength and UV aging resistance of concrete, delays the occurrence of road cracks, and enhances the stability and durability of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses anti-rutting epoxy resin concrete, and relates to the technical field of concrete materials. According to the invention, rice husk carbon composite silicon dioxide nanospheres are modified by using 2-aminoethylaminomethyltriethoxysilane, and are subjected to melt spinning with epoxy resin and hexahydrophthalic anhydride, formed epoxy resin fibers are interspersed in concrete to play a supporting structure, and meanwhile, due to the existence of the rigid rice husk carbon composite silicon dioxide nanospheres, the concrete can be well supported by the epoxy resin fibers; craze expansion caused by external force can be inhibited, the fiber balling effect can be avoided, and the compressive strength of the concrete is improved; 2, 4-dihydroxybenzophenone and amino polyethylene glycol acrylate are utilized to form a conjugated system in the asphalt, a strong anti-ultraviolet effect is achieved, the compatibility of the asphalt and epoxy resin is enhanced with the help of calcium ions, and then the anti-ultraviolet and anti-compression effects are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, in particular to anti-rutting epoxy resin concrete. Background Art

[0002] Due to the continuous development of society, the government has invested a lot of money to strengthen the country's infrastructure. Many cities or rural areas are building roads, and the demand for concrete floors is gradually increasing. However, on the market, general concrete floors are currently made of cement and sand, and such floors have low compressive strength and do not meet market demand. Secondly, coupled with ultraviolet aging caused by sunlight, its ductility decreases, which can easily cause cracks in the road surface, especially at intersections, bus ports, uphill and downhill locations; therefore, it is particularly important to invent a rutting-resistant concrete. Summary of the invention

[0003] The object of the present invention is to provide an anti-rutting epoxy resin concrete and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an anti-rutting epoxy resin concrete, which is made of epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpene saponin air entraining agent, melamine water reducer and deionized water.

[0005] Furthermore, the epoxy resin fiber is prepared by melt spinning modified rice husk charcoal composite silica nanospheres, hexahydrophthalic anhydride and epoxy resin E51.

[0006] Furthermore, the modified rice husk charcoal composite silica nanospheres are prepared from rice husk charcoal composite silica nanospheres modified by 2-aminoethylaminomethyltriethoxysilane.

[0007] Furthermore, the modified asphalt is prepared by modifying asphalt with modified 2,4-dihydroxybenzophenone and calcium chloride.

[0008] Furthermore, the modified 2,4-dihydroxybenzophenone is prepared from 2,4-dihydroxybenzophenone and amino polyethylene glycol acrylate.

[0009] Furthermore, a method for preparing anti-rutting epoxy resin concrete comprises the following preparation steps: (1) Mix rice husk powder, sodium hydroxide and deionized water in a mass ratio of 0.8:0.8:3.6-1.2:1.2:4.4, stir evenly, heat to 70-90°C, stir at 100-200 rpm for 4-6 hours, cool to room temperature, filter, take solid, wash with deionized water 4-8 times, vacuum dry at 50-70°C for 10-15 hours, grind until it passes through a 400-800 mesh sieve, add methanol 2-4 times the mass of rice husk powder, ethyl orthosilicate 3-6 times the mass of rice husk powder, and 0.8 mol / L dilute hydrochloric acid 1-2 times the mass of rice husk powder, stir at 250-300 rpm for 30-60 hours, filter, take solid, wash with deionized water 2-5 times, dry at -45--50°C for 20-26 hours, and calcine at 700-800°C for 4-8 hours to obtain rice husk carbon composite silica nanospheres; (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass of 25 to 30 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 95 to 105°C under nitrogen protection, stir at 70 to 100 rpm for 10 to 14 hours, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and vacuum dry it at 80 to 110°C for 3 to 6 hours to obtain modified rice husk charcoal composite silica nanospheres; (3) Mix epoxy resin E51 and hexahydrophthalic anhydride, stir at 70-100 rpm for 10-30 min, ultrasonicate at 20-40 kHz for 60-100 min, add n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres, stir at 100-200 rpm for 3-6 h, perform melt spinning, and cure at 90-120 ° C for 3-6 h to obtain epoxy resin fibers; (4) Mix 2,4-dihydroxybenzophenone and anhydrous ethanol in a mass ratio of 20:95 to 24:110 and place in an ice water bath at 0 to 4°C, add 8wt% sodium hydroxide aqueous solution at a rate of 0.3 to 0.7 mL / s in an amount of 5.4 to 7.2 times the mass of 2,4-dihydroxybenzophenone, react for 30 to 60 min, add dimethyl sulfate at a mass of 1.5 to 2 times the mass of 2,4-dihydroxybenzophenone, stir at 70 to 100 rpm for 10 to 14 h, filter, take the solid, and wash it with 8wt% sodium hydroxide aqueous solution and anhydrous ethanol for 2 to 4 times respectively to obtain intermediate A; (5) Mix intermediate A and N,N-dimethylformamide in a mass ratio of 9:4 to 10:6, and stir at 70 to 100 rpm for 20 to 30 min to obtain a mixed solution; place N,N-dimethylformamide in an ice water bath at 0 to 4°C, and add a mixed solution of 0.9 to 1.1 times the mass of N,N-dimethylformamide and 2.8 to 3.4 times the mass of N,N-dimethylformamide dropwise at a rate of 0.1 to 0.3 mL / s; Heat to 70-80°C, react for 3-6 hours, cool to room temperature, add 20-25 times the mass of N,N-dimethylformamide, 0-4°C deionized water and 1-1.5 times the mass of N,N-dimethylformamide, 10wt% sodium carbonate aqueous solution, filter, take the solid, wash with deionized water 1-3 times, add 4-7 times the mass of N,N-dimethylformamide, anhydrous ethanol, let stand for 1-2 hours, filter, take the solid, and obtain intermediate B; (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane are mixed in a mass ratio of 1.5:1:13 to 3:1.7:17, stirred at 70 to 100 rpm for 3 to 6 hours, 6 to 8 times the mass of dichloromethane, 0 to 4°C deionized water is added, and the solution is adjusted to pH 5 with hydrochloric acid, filtered, the solid is taken, washed with saturated sodium chloride solution 1 to 3 times, 5 wt% sodium hydroxide aqueous solution is added to the solution until the pH value is 8 to 10, and then dilute hydrochloric acid is added to the solution until the pH value is 5 to 6, and the solution is allowed to stand for 30 to 60 minutes, filtered, the solid is taken, washed with deionized water 1 to 3 times, and dried at 50 to 70°C for 3 to 6 hours to obtain modified 2,4-dihydroxybenzophenone; (7) Mix amino polyethylene glycol acrylate, distilled water and anhydrous ethanol in a mass ratio of 0.8:0.8:16 to 1.2:1.2:24, add modified 2,4-dihydroxybenzophenone in an amount of 4 to 8 times the mass of amino polyethylene glycol acrylate, stir at 70 to 100 rpm for 4 to 6 hours, add 0.5 mol / L calcium chloride aqueous solution in an amount of 4 to 6 times the mass of amino polyethylene glycol acrylate, soak at 33 to 40°C for 3 days, then add No. 90 base asphalt in an amount of 36 to 44 times the mass of amino polyethylene glycol acrylate and hexadecyltrimethylammonium chloride in an amount of 5 to 10 times the mass of amino polyethylene glycol acrylate, heat to 130 to 160°C, stir at 3000 to 5000 rpm for 20 to 40 minutes to obtain modified asphalt; (8) Mix the epoxy resin fiber and modified asphalt, heat to 105-130°C, stir at 150-250 rpm for 4-8 h, let stand for 1-2 h, add silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water, stir at 20-30 Hz and 100-200 rpm for 30-50 min, and obtain rutting-resistant epoxy resin concrete.

[0010] Furthermore, the vacuum degree in step (1) and step (2) is both 0.2 to 1 kPa.

[0011] Furthermore, the melt spinning conditions in step (3) are: temperature of 190-230° C., melt viscosity of 200-250 Pa×s, and tensile strength of 8.8-11.5 MPa.

[0012] Furthermore, in step (3), the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres is 50:46.5:2.3:5 to 70:68.2:4.2:8.

[0013] Furthermore, in step (8), the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer and deionized water is 1:120:48:160:134:17:1:0.5:30-2:160:56:180:154:21:1.2:0.7:40.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The concrete of the invention is prepared by mixing epoxy resin fiber and modified asphalt to achieve the effects of compression resistance and UV resistance.

[0015] Firstly, the present invention uses rice husk charcoal to load on mesoporous silica to improve the rigidity and hardness of silica, and indirectly improve the compressive strength of concrete; then, 2-aminoethylaminomethyltriethoxysilane is used to modify it, and after melt spinning with epoxy resin and hexahydrophthalic anhydride, heat treatment is performed to open the amino group of 2-aminoethylaminomethyltriethoxysilane and the epoxy group to form a covalent bond link, thereby generating a strong interfacial tension; when subjected to external force, the interface between the rigid rice husk charcoal composite silica nanosphere and the resin matrix is ​​destroyed to absorb a large amount of energy, and the generated holes make the concrete ... The local strain capacity of the epoxy resin cross-linked network is improved, the stress transfer is more uniform, and the expansion of silver streaks in the resin matrix can be effectively inhibited, thereby strengthening the epoxy resin and indirectly improving the compressive strength of the concrete. At the same time, the hydroxyl groups produced by the ring opening react with the anhydride groups of hexahydrophthalic anhydride, thereby increasing the three-dimensional cross-linking degree inside the epoxy resin fiber and forming a more stable structural morphology, which is interspersed in the concrete to play a supporting structure. With the assistance of nanospheres, the fiber balling effect is effectively prevented, which is equivalent to a secondary reinforcement effect and greatly improves the compressive strength of the concrete.

[0016] Secondly, an aldehyde group is introduced into the benzene ring of 2,4-dihydroxybenzophenone, and then an addition dehydration reaction is carried out with the amino group in aminopolyethylene glycol acrylate to introduce carbon-nitrogen double bonds, carbon-carbon double bonds and benzene rings to form a conjugated system in the asphalt, which can shield and absorb ultraviolet rays, so that the matrix can achieve a strong anti-ultraviolet effect. Then, the hydroxyl group is combined with calcium ions to stimulate the adhesion between the asphalt and the rigid particles in the epoxy resin fiber, so that the asphalt particles serve as the connection point of the epoxy resin fiber "bridge", thereby forming a dense and locked structure inside the concrete, jointly bearing external forces, and significantly improving the mechanical properties of the concrete and enhancing the compressive resistance. At the same time, the compatibility between aminopolyethylene glycol acrylate and asphalt is also enhanced, thereby enhancing the anti-ultraviolet effect of the concrete. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-rutting epoxy resin concrete prepared in the following examples are as follows: Rutting resistance: The concrete of the embodiment and the comparative example was made into specimens with a thickness of 80 mm, and the dynamic stability of the specimens was tested with reference to JTG E20.

[0019] Compression resistance: The concrete of the embodiment and the comparative example was made into specimens with a size of 100 mm×100 mm×100 mm, and the compressive strength test of the specimens at different ages was carried out with reference to GB / T50081.

[0020] Anti-ultraviolet: Take the embodiment and comparative example of the same size and conduct carbonization test according to GB / T50082.

[0021] Example 1 (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 0.8:0.8:3.6, stirred evenly, heated to 70°C, stirred at 100 rpm for 4 h, cooled to room temperature, filtered, the solid was washed with deionized water for 4 times, dried at 50°C and a vacuum degree of 0.2 kPa for 10 h, ground until it passed through a 400-mesh sieve, and methanol (2 times the mass of rice husk powder), ethyl orthosilicate (3 times the mass of rice husk powder) and 0.8 mol / L dilute hydrochloric acid (1 times the mass of rice husk powder) were added, stirred at 250 rpm for 30 h, filtered, the solid was washed with deionized water twice, dried at -45°C for 20 h, and calcined at 700°C for 4 h to obtain rice husk carbon composite silica nanospheres; (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass 25 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 95°C under nitrogen protection, stir at 70 rpm for 10 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and dry it at 80°C and a vacuum degree of 0.2 kPa for 3 h to obtain modified rice husk charcoal composite silica nanospheres; (3) The epoxy resin E51 was mixed with hexahydrophthalic anhydride, stirred at 70 rpm for 10 min, ultrasonicated at 20 kHz for 60 min, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres were added, stirred at 100 rpm for 3 h, extruded and spun at a temperature of 190 ° C, a melt viscosity of 200 Pa × s, and a tensile strength of 8.8 MPa, and cured at 90 ° C for 3 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 50:46.5:2.3:5; (4) 2,4-dihydroxybenzophenone and anhydrous ethanol were mixed in a mass ratio of 20:95 and placed in an ice water bath at 0°C. An 8 wt % sodium hydroxide aqueous solution (5.4 times the mass of 2,4-dihydroxybenzophenone) was added dropwise at 0.3 mL / s. The mixture was reacted for 30 min. Dimethyl sulfate (1.5 times the mass of 2,4-dihydroxybenzophenone) was added. The mixture was stirred at 70 rpm for 10 h. The mixture was filtered and the solid was taken. The solid was washed twice with an 8 wt % sodium hydroxide aqueous solution and anhydrous ethanol respectively to obtain intermediate A. (5) Mix intermediate A and N,N-dimethylformamide in a mass ratio of 9:4, stir at 70 rpm for 20 min to obtain a mixed solution; put N,N-dimethylformamide in a 0°C ice-water bath, add a mixed solution of 0.9 times the mass of N,N-dimethylformamide in a volume of phosphorus oxychloride and 2.8 times the mass of N,N-dimethylformamide at a rate of 0.1 mL / s, heat to 70°C, react for 3 h, cool to room temperature, add 20 times the mass of N,N-dimethylformamide in 0°C deionized water and 1 times the mass of N,N-dimethylformamide in a volume of 10 wt% sodium carbonate aqueous solution, filter, take the solid, wash once with deionized water, add 4 times the mass of N,N-dimethylformamide in anhydrous ethanol, let stand for 1 h, filter, take the solid, and obtain intermediate B; (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 1.5:1:13, stirred at 70 rpm for 3 h, 6 times the mass of dichloromethane and 0°C deionized water were added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed once with saturated sodium chloride solution, 5 wt% sodium hydroxide aqueous solution was added until the solution pH was 8, and then dilute hydrochloric acid was added until the solution pH was 5, allowed to stand for 30 min, filtered, the solid was taken, washed once with deionized water, and dried at 50°C for 3 h to obtain modified 2,4-dihydroxybenzophenone; (7) Mix amino polyethylene glycol acrylate, distilled water and anhydrous ethanol in a mass ratio of 0.8:0.8:16, add modified 2,4-dihydroxybenzophenone 4 times the mass of amino polyethylene glycol acrylate, stir at 70 rpm for 4 h, add 0.5 mol / L calcium chloride aqueous solution 4 times the mass of amino polyethylene glycol acrylate, soak at 33°C for 3 days, then add No. 90 base asphalt 36 times the mass of amino polyethylene glycol acrylate and hexadecyltrimethylammonium chloride 5 times the mass of amino polyethylene glycol acrylate, heat to 130°C, stir at 3000 rpm for 20 min, and obtain modified asphalt; (8) Mix the epoxy resin fiber and modified asphalt, heat to 105°C, stir at 150 rpm for 4 h, let stand for 1 h, add silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water, and stir at 20 Hz and 100 rpm for 30 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 1:120:48:160:134:17:1:0.5:30.

[0022] Example 2 (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 1:1:4, stirred evenly, heated to 80°C, stirred at 150 rpm for 5 h, cooled to room temperature, filtered, the solid was washed with deionized water for 6 times, dried at 60°C and a vacuum degree of 0.6 kPa for 12.5 h, ground until it passed through a 600-mesh sieve, and methanol (3 times the mass of rice husk powder), ethyl orthosilicate (4.5 times the mass of rice husk powder) and 0.8 mol / L dilute hydrochloric acid (1.5 times the mass of rice husk powder) were added, stirred at 275 rpm for 45 h, filtered, the solid was washed with deionized water for 4 times, dried at -47.5°C for 24 h, and calcined at 750°C for 6 h to obtain rice husk carbon composite silica nanospheres; (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass 27 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 100°C under nitrogen protection, stir at 85 rpm for 12 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and dry it at 95°C and a vacuum degree of 0.6 kPa for 4.5 h to obtain modified rice husk charcoal composite silica nanospheres; (3) The epoxy resin E51 was mixed with hexahydrophthalic anhydride, stirred at 85 rpm for 20 min, ultrasonicated at 30 kHz for 80 min, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres were added, stirred at 150 rpm for 4.5 h, extruded and spun at a temperature of 210 ° C, a melt viscosity of 225 Pa × s, and a tensile strength of 10.25 MPa, and cured at 110 ° C for 4.5 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 60:57.5:3.2:6.5; (4) 2,4-dihydroxybenzophenone and anhydrous ethanol were mixed in a mass ratio of 22:103, placed in an ice water bath at 0-4°C, and an 8 wt% sodium hydroxide aqueous solution (6.3 times the mass of 2,4-dihydroxybenzophenone) was added dropwise at 0.5 mL / s, and the mixture was reacted for 45 min. Dimethyl sulfate (1.75 times the mass of 2,4-dihydroxybenzophenone) was added, and the mixture was stirred at 85 rpm for 12 h. The mixture was filtered, and the solid was taken and washed three times with an 8 wt% sodium hydroxide aqueous solution and anhydrous ethanol, respectively, to obtain intermediate A. (5) Mix intermediate A and N,N-dimethylformamide in a mass ratio of 9.5:5, stir at 85 rpm for 25 min to obtain a mixed solution; put N,N-dimethylformamide in a 2°C ice water bath, add phosphorus oxychloride (1 times the mass of N,N-dimethylformamide) dropwise at 0.2 mL / s, add the mixed solution (3.1 times the mass of N,N-dimethylformamide), heat to 75°C, react for 4.5 h, cool to room temperature, add 22.5 times the mass of N,N-dimethylformamide, 2°C deionized water and 1.25 times the mass of N,N-dimethylformamide, add 10 wt% sodium carbonate aqueous solution, filter, take the solid, wash twice with deionized water, add anhydrous ethanol (5.5 times the mass of N,N-dimethylformamide), let stand for 1.5 h, filter, take the solid, and obtain intermediate B; (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 2.25:1.3:15, stirred at 85 rpm for 4 h, 7 times the mass of dichloromethane and 2°C deionized water was added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed twice with saturated sodium chloride solution, 5 wt% sodium hydroxide aqueous solution was added until the solution pH was 9, and then dilute hydrochloric acid was added until the solution pH was 5.5, allowed to stand for 45 min, filtered, the solid was taken, washed twice with deionized water, and dried at 60°C for 4.5 h to obtain modified 2,4-dihydroxybenzophenone; (7) Mix amino polyethylene glycol acrylate, distilled water and anhydrous ethanol in a mass ratio of 1:1:20, add modified 2,4-dihydroxybenzophenone 6 times the mass of amino polyethylene glycol acrylate, stir at 85 rpm for 5 h, add 0.5 mol / L calcium chloride aqueous solution 5 times the mass of amino polyethylene glycol acrylate, soak at 37°C for 3 d, then add No. 90 base asphalt 40 times the mass of amino polyethylene glycol acrylate and hexadecyltrimethylammonium chloride 7.5 times the mass of amino polyethylene glycol acrylate, heat to 145°C, stir at 4000 rpm for 30 min, and obtain modified asphalt; (8) Mix the epoxy resin fiber and modified asphalt, heat to 117.5°C, stir at 200 rpm for 6 h, let stand for 1.5 h, add silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water, and stir at 25 Hz and 150 rpm for 40 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 1.5:140:52:170:144:19:1.1:0.6:35.

[0023] Example 3 (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 1.2:1.2:4.4, stirred evenly, heated to 90°C, stirred at 200 rpm for 6 h, cooled to room temperature, filtered, the solid was washed with deionized water 8 times, dried at 70°C and vacuum degree of 1 kPa for 15 h, ground until it passed through an 800-mesh sieve, and methanol 4 times the mass of rice husk powder, ethyl orthosilicate 6 times the mass of rice husk powder, and 0.8 mol / L dilute hydrochloric acid 2 times the mass of rice husk powder were added, stirred at 300 rpm for 60 h, filtered, the solid was washed with deionized water 5 times, dried at -50°C for 26 h, and calcined at 800°C for 8 h to obtain rice husk carbon composite silica nanospheres; (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass 30 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 105°C under nitrogen protection, stir at 100 rpm for 14 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and dry it at 110°C and a vacuum degree of 1 kPa for 6 h to obtain modified rice husk charcoal composite silica nanospheres; (3) The epoxy resin E51 was mixed with hexahydrophthalic anhydride, stirred at 100 rpm for 30 min, ultrasonicated at 40 kHz for 100 min, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres were added, stirred at 200 rpm for 6 h, extruded and spun at a temperature of 230 ° C, a melt viscosity of 250 Pa × s, and a tensile strength of 11.5 MPa, and cured at 120 ° C for 6 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 70:68.2:4.2:8; (4) 2,4-dihydroxybenzophenone and anhydrous ethanol were mixed in a mass ratio of 24:110, placed in a 4°C ice-water bath, and an 8 wt% sodium hydroxide aqueous solution (7.2 times the mass of 2,4-dihydroxybenzophenone) was added dropwise at 0.7 mL / s, and the mixture was reacted for 60 min. Dimethyl sulfate (2 times the mass of 2,4-dihydroxybenzophenone) was added, and the mixture was stirred at 100 rpm for 14 h. The mixture was filtered, and the solid was taken and washed 4 times with an 8 wt% sodium hydroxide aqueous solution and 4 times with anhydrous ethanol, respectively, to obtain intermediate A. (5) Mix intermediate A and N,N-dimethylformamide in a mass ratio of 10:6, and stir at 100 rpm for 30 min to obtain a mixed solution; place N,N-dimethylformamide in a 4°C ice water bath, add a mixed solution of phosphorus oxychloride (1.1 times the mass of N,N-dimethylformamide) and 3.4 times the mass of N,N-dimethylformamide at a rate of 0.3 mL / s, heat to 80°C, react for 6 h, cool to room temperature, add 25 times the mass of N,N-dimethylformamide, 4°C deionized water and 1.5 times the mass of N,N-dimethylformamide, 10 wt% sodium carbonate aqueous solution, filter, take the solid, wash with deionized water 3 times, add anhydrous ethanol (7 times the mass of N,N-dimethylformamide), let stand for 2 h, filter, take the solid, and obtain intermediate B; (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 3:1.7:17, stirred at 100 rpm for 6 h, 8 times the mass of dichloromethane, 4°C deionized water was added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed with saturated sodium chloride solution 3 times, 5 wt% sodium hydroxide aqueous solution was added until the solution pH was 10, and then dilute hydrochloric acid was added until the solution pH was 6, allowed to stand for 60 min, filtered, the solid was taken, washed with deionized water 3 times, and dried at 70°C for 6 h to obtain modified 2,4-dihydroxybenzophenone; (7) Mix amino polyethylene glycol acrylate, distilled water and anhydrous ethanol in a mass ratio of 1.2:1.2:24, add modified 2,4-dihydroxybenzophenone in an amount of 8 times the mass of amino polyethylene glycol acrylate, stir at 100 rpm for 6 h, add 0.5 mol / L calcium chloride aqueous solution in an amount of 6 times the mass of amino polyethylene glycol acrylate, soak at 40°C for 3 days, then add No. 90 base asphalt in an amount of 44 times the mass of amino polyethylene glycol acrylate and hexadecyltrimethylammonium chloride in an amount of 10 times the mass of amino polyethylene glycol acrylate, heat to 160°C, stir at 5000 rpm for 40 min, and obtain modified asphalt; (8) Mix the epoxy resin fiber and modified asphalt, heat to 130°C, stir at 250 rpm for 8 h, let stand for 2 h, add silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water, and stir at 30 Hz and 200 rpm for 50 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 2:160:56:180:154:21:1.2:0.7:40.

[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) and step (2) are omitted, and step (3) is changed to: epoxy resin E51 and hexahydrophthalic anhydride are mixed, stirred at 85 rpm for 20 min, ultrasonicated at 30 kHz for 80 min, extruded and spun at a temperature of 210° C., a melt viscosity of 225 Pa×s, and a tensile strength of 10.25 MPa, and cured at 110° C. for 4.5 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51 to the hexahydrophthalic anhydride is 60:57.5; and the remaining steps are the same as those of Example 2.

[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (2) is changed to: silica nanospheres and 2-aminoethylaminomethyltriethoxysilane are mixed in a mass ratio of 1:1, placed in toluene with a mass 27 times that of 2-aminoethylaminomethyltriethoxysilane, heated to 100° C. under nitrogen protection, stirred at 85 rpm for 12 h, filtered, and the solid was taken, washed twice with dichloromethane and ethanol respectively, and dried at 95° C. and a vacuum degree of 0.6 kPa for 4.5 h to obtain modified silica nanospheres; step (3) is changed to: epoxy resin E51 and hexahydrophthalic anhydride The mixture was mixed, stirred at 85 rpm for 20 min, and ultrasonicated at 30 kHz for 80 min. n-butyl glycidyl ether and modified silica nanospheres were added, and stirred at 150 rpm for 4.5 h. Extrusion spinning was performed at a temperature of 210° C., a melt viscosity of 225 Pa×s, and a tensile strength of 10.25 MPa. The mixture was cured at 110° C. for 4.5 h to obtain epoxy resin fibers. The mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 60:57.5:3.2:6.5. The remaining steps were the same as those in Example 2.

[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: epoxy resin E51, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres are mixed, stirred at 150 rpm for 4.5 h, extruded and spun at a temperature of 210° C., a melt viscosity of 225 Pa×s, and a tensile strength of 10.25 MPa, and cured at 110° C. for 4.5 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres is 60:3.2:6.5; the remaining steps are the same as in Example 2.

[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that step (1), step (2) and step (3) are omitted, and step (8) is changed to: modified asphalt, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water are stirred at 25 Hz and 150 rpm for 40 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the modified asphalt, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 140:52:170:144:19:1.1:0.6:35; the remaining steps are the same as those in Example 2.

[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that step (4), step (5), step (6) and step (7) are omitted; step (8) is changed to: epoxy resin fiber, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer and deionized water are stirred at 25 Hz and 150 rpm for 40 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the epoxy resin fiber, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer and deionized water is 1.5:52:170:144:19:1.1:0.6:35; the remaining steps are the same as those in Example 2.

[0029] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that steps (4), (5) and step (6) are omitted, and step (7) is changed to: 2,4-dihydroxybenzophenone and a 0.5 mol / L calcium chloride aqueous solution with a mass of 5 times that of 2,4-dihydroxybenzophenone are soaked at 37° C. for 3 days, and then No. 90 base asphalt with a mass of 40 times that of 2,4-dihydroxybenzophenone and hexadecyltrimethylammonium chloride with a mass of 7.5 times that of 2,4-dihydroxybenzophenone are added, the temperature is raised to 145° C., and the mixture is stirred at 4000 rpm for 30 minutes to obtain modified asphalt; the remaining steps are the same as those in Example 2.

[0030] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that step (7) is different. Step (7) is changed to: amino polyethylene glycol acrylate, distilled water and anhydrous ethanol are mixed in a mass ratio of 1:1:20, modified 2,4-dihydroxybenzophenone is added in an amount of 6 times the mass of amino polyethylene glycol acrylate, and stirred at 85 rpm for 5 h, No. 90 base asphalt is added in an amount of 40 times the mass of amino polyethylene glycol acrylate and hexadecyltrimethylammonium chloride is added in an amount of 7.5 times the mass of amino polyethylene glycol acrylate, the temperature is raised to 145°C, and stirred at 4000 rpm for 30 min to obtain modified asphalt; the remaining steps are the same as those in Example 2.

[0031] Effect example Table 1 below shows the performance analysis results of the rutting-resistant epoxy resin concrete using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.

[0032] Table 1 From the comparison of the compressive strength test data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses 2-aminoethylaminomethyltriethoxysilane to modify the rice husk carbon silicon composite silica nanospheres, and after melt spinning with epoxy resin and hexahydrophthalic anhydride, heat treatment is performed to form covalent bonds, which can absorb a large amount of energy and generate holes when subjected to external force, so that the local strain capacity of the epoxy resin cross-linking network is improved, the expansion of silver streaks in the matrix is ​​effectively suppressed, and the role of strengthening the epoxy resin is played, thereby achieving the effect of compressive resistance; at the same time, with the assistance of the nanospheres, the epoxy resin fibers are interspersed in the interior of the concrete to form A stable three-dimensional cross-linked structure is formed to support the structure and enhance the compressive resistance of the concrete. From the comparison of the carbonization depth data of the embodiment and the comparative example in Table 1, it can be found that the aldehyde group introduced by 2,4-dihydroxybenzophenone reacts with aminopolyethylene glycol acrylate to form a conjugated system in the asphalt, which shields and absorbs ultraviolet rays and achieves a strong anti-ultraviolet effect. Then, the hydroxyl group is combined with calcium ions to form a dense and locked structure inside the concrete, which jointly bears external forces and enhances compressive resistance. At the same time, the compatibility of aminopolyethylene glycol acrylate and asphalt is also enhanced, thereby enhancing the anti-ultraviolet effect of the concrete.

[0033] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An anti-rutting epoxy resin concrete, characterized in that: The anti-rutting epoxy resin concrete is prepared from epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water; the preparation method of the anti-rutting epoxy resin concrete comprises the following preparation steps: (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 1:1:4, stirred evenly, heated to 80°C, stirred at 150 rpm for 5 h, cooled to room temperature, filtered, the solid was washed with deionized water for 6 times, dried at 60°C and a vacuum degree of 0.6 kPa for 12.5 h, ground until it passed through a 600-mesh sieve, and methanol (3 times the mass of rice husk powder), ethyl orthosilicate (4.5 times the mass of rice husk powder) and 0.8 mol / L dilute hydrochloric acid (1.5 times the mass of rice husk powder) were added, stirred at 275 rpm for 45 h, filtered, the solid was washed with deionized water for 4 times, dried at -47.5°C for 24 h, and calcined at 750°C for 6 h to obtain rice husk carbon composite silica nanospheres; (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass 27 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 100°C under nitrogen protection, stir at 85 rpm for 12 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and dry it at 95°C and a vacuum degree of 0.6 kPa for 4.5 h to obtain modified rice husk charcoal composite silica nanospheres; (3) The epoxy resin E51 was mixed with hexahydrophthalic anhydride, stirred at 85 rpm for 20 min, ultrasonicated at 30 kHz for 80 min, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres were added, stirred at 150 rpm for 4.5 h, extruded and spun at a temperature of 210 ° C, a melt viscosity of 225 Pa × s, and a tensile strength of 10.25 MPa, and cured at 110 ° C for 4.5 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 60:57.5:3.2:6.5; (4) 2,4-dihydroxybenzophenone and anhydrous ethanol were mixed in a mass ratio of 22:103, placed in an ice water bath at 0-4°C, and an 8 wt% sodium hydroxide aqueous solution (6.3 times the mass of 2,4-dihydroxybenzophenone) was added dropwise at 0.5 mL / s, and the mixture was reacted for 45 min. Dimethyl sulfate (1.75 times the mass of 2,4-dihydroxybenzophenone) was added, and the mixture was stirred at 85 rpm for 12 h. The mixture was filtered, and the solid was taken and washed three times with an 8 wt% sodium hydroxide aqueous solution and anhydrous ethanol, respectively, to obtain intermediate A. (5) Mix intermediate A and N,N-dimethylformamide in a mass ratio of 9.5:5, stir at 85 rpm for 25 min to obtain a mixed solution; put N,N-dimethylformamide in a 2°C ice water bath, add phosphorus oxychloride (1 times the mass of N,N-dimethylformamide) dropwise at 0.2 mL / s, add the mixed solution (3.1 times the mass of N,N-dimethylformamide), heat to 75°C, react for 4.5 h, cool to room temperature, add 22.5 times the mass of N,N-dimethylformamide, 2°C deionized water and 1.25 times the mass of N,N-dimethylformamide, add 10 wt% sodium carbonate aqueous solution, filter, take the solid, wash twice with deionized water, add anhydrous ethanol (5.5 times the mass of N,N-dimethylformamide), let stand for 1.5 h, filter, take the solid, and obtain intermediate B; (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 2.25:1.3:15, stirred at 85 rpm for 4 h, 7 times the mass of dichloromethane and 2°C deionized water was added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed twice with saturated sodium chloride solution, 5 wt% sodium hydroxide aqueous solution was added until the solution pH was 9, and then dilute hydrochloric acid was added until the solution pH was 5.5, allowed to stand for 45 min, filtered, the solid was taken, washed twice with deionized water, and dried at 60°C for 4.5 h to obtain modified 2,4-dihydroxybenzophenone; (7) Mix amino polyethylene glycol acrylate, distilled water and anhydrous ethanol in a mass ratio of 1:1:20, add modified 2,4-dihydroxybenzophenone 6 times the mass of amino polyethylene glycol acrylate, stir at 85 rpm for 5 h, add 0.5 mol / L calcium chloride aqueous solution 5 times the mass of amino polyethylene glycol acrylate, soak at 37°C for 3 d, then add No. 90 base asphalt 40 times the mass of amino polyethylene glycol acrylate and hexadecyltrimethylammonium chloride 7.5 times the mass of amino polyethylene glycol acrylate, heat to 145°C, stir at 4000 rpm for 30 min, and obtain modified asphalt; (8) Mix the epoxy resin fiber and modified asphalt, heat to 117.5°C, stir at 200 rpm for 6 h, let stand for 1.5 h, add silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water, and stir at 25 Hz and 150 rpm for 40 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 1.5:140:52:170:144:19:1.1:0.6:35.